Level of Knowledge and Self Efficacy Improve Breast Self-Examination (BSE) Behaviors (KEMAS: Jurnal Kesehatan Masyarakat, 2023)
The incidence of breast cancer is 40 per 100.000 women. BSE is a screening to detect breast cancer. The research objective is to determine the correlation between knowledge and self-efficacy with BSE behavior. This cross-sectional descriptive-analytic study utilized a sample of 20-65 women aged 100 years. Multistage random sampling was used as the sampling technique—univariate and bivariate analysis with a significance level of ρ 0.05 and CI of 95%. The analysis results showed a correlation between the level of knowledge and self-efficacy with BSE behavior (p-value = 0.026; 0.021) and PR values of 2.5 and 2.6 (CI 95%: 1.074-5.641; 1.100- 6.293). In conclusion, women who have a high level of knowledge and self-efficacy are three times more likely to do BSE compared to women with low levels of knowledge and self-efficacy.